(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to determine that the STEM approach can overcome the low ability to think creatively by applying the STEM approach how the steps of the STEM approach are used in the learning process about material on curved face three dimensional object (cylinder). The method used in this research is descriptive qualitative. This study used a purposive sampling and data collection techniques used are observation, creative thinking skills tests, and interviews. The instruments used in this study are observation sheets, test sheets of students’ creative thinking skills on the material of curved face three dimensional object (cylinder), and interview guidelines. The cause of students’ creative thinking abilities is low because students consider that mathematics is difficult and not a pleasant lesson. Students also feel bored and bored with the learning process by the teacher who is still dominant using the lecture method. However, these problems can be resolved after the teacher has learned using the STEM approach. Therefore, it can be concluded that the learning process that applies the STEM approach can overcome the low ability of students’ creative thinking on the material of curved face three .dimensional .object (cylinder).